Sertifikasi dan Pelatihan Video Editor Bagi Siswa Multimediasmk N H. Moenadi - Atmaja Septa Miyosa; Surasa Surasa; Sarwanto Sarwanto; Priya Wintar Yuhanto (Jurnal Abdimas ADPI Sains dan Teknologi, 2022)
The Video editor certification and training was carried out at SMK Negeri H. Moenadi Ungaran, Central Java by a lecturer in the animation study program at the Multi Media High School on August 15 to 20, 2022. The formulation of the problem is the student's need for competency certificates with the Video Editor scheme. The purpose of the training is to improve video editing skills followed by a competency test. The methods used are lectures, demonstrations and competency tests. The main material presented is Introduction to Production, Writing Documentary Video Production Scripts, Introduction to Video Cameras, Audio, and Lighting, Non Linear Editing. The practice of taking pictures is carried out entirely within the school environment. The results of the training are in the form of video editing works as well as competency certificates for those declared competent by the assessors.